Comparative efficacy of bariatric endoscopic procedures in the treatment of morbid obesity: a systematic review and network meta-analysis - Jung, Sung Hoon; Yoon, Jai Hoon; Choi, Hyuk Soon; Nam, Seung-Joo; Kim, Kyoung Oh; Kim, Do Hoon; Kim, Jung-Wook; Sohn, Won; Hyun, Yil Sik; Park, Chan Hyuk; Lee, Hang Lak; for the Korean Research Group for Endoscopic Management of Metabolic Disorder and Obesity (Endoscopy, 2020)
Background The comparative efficacy of bariatric endoscopic procedures has not been completely elucidated. We aimed to comprehensively evaluate the efficacy of bariatric endoscopic procedures.Methods We searched for randomized controlled trials investigating the efficacy of bariatric endoscopic procedures, including the use of an intragastric balloon, duodenal-jejunal bypass liner (DJBL), aspiration therapy, primary obesity surgery endoluminal (POSE) procedure, and botulinum toxin injection to the stomach. Network meta-analyses were performed to determine the percentage of weight loss (%weight loss) and percentage of excess weight loss (%EWL).Results 22 studies with 2141 patients were included in the meta-analysis. Most endoscopic procedures showed superior efficacy in terms of %weight loss compared with the control (mean difference [MD] [95 % confidence interval (CI)]: aspiration therapy 10.4 % [7.0 % to 13.7 %]; fluid-filled balloon 5.3 % [3.4 % to 7.2 %]; POSE 4.9 % [1.7 % to 8.2 %]; and DJBL 4.5 % [1.4 % to 7.7 %]). In terms of %EWL, aspiration therapy, fluid-filled balloon, POSE, and DJBL were superior to the control (MD [95 %CI]: 27.3 % [15.3 % to 39.3 %]; 22.4 % [15.4 % to 29.4 %]; 15.3 % [2.5 % to 28.0 %]; and 13.0 % [4.9 % to 21.2], respectively). The gas-filled balloon and botulinum toxin injection did not show a significant difference in %weight loss or %EWL compared with the control. For the fluid-filled balloon, the %EWL and %weight loss tended to decrease after balloon removal at 6 months after the procedure.Conclusion All bariatric endoscopic procedures, except for gas-filled balloon and botulinum toxin injection to the stomach, showed superior short-term efficacy in terms of %weight loss or %EWL compared with lifestyle modification.